Search for a massive resonance decaying into a Higgs boson and a W or Z boson in hadronic final states in proton-proton collisions at $ \sqrt{s}=8 $ TeV - CMS collaboration (2275 authors) (2016)
A search for a massive resonance decaying into a standard-model-like Higgs boson (H) and a W or Z boson is reported. The analysis is performed on a data sample corresponding to an integrated luminosity of 19.7 fb$^{−1}$, collected in proton-proton collisions at a centre-of-mass energy of 8 TeV with the CMS detector at the LHC. Signal events, in which the decay products of Higgs, W, or Z bosons at high Lorentz boost are contained within single reconstructed jets, are identified using jet substructure techniques, including the tagging of b hadrons. This is the first search for heavy resonances decaying into HW or HZ resulting in an all-jet final state, as well as the first application of jet substructure techniques to identify H → WW$^{*}$ → 4q decays at high Lorentz boost. No significant signal is observed and limits are set at 95% confidence level on the production cross sections of W′ and Z′ in a model with mass-degenerate charged and neutral spin-1 resonances. Resonance masses are excluded for W′ in the interval [1.0, 1.6] TeV, for Z$^{′}$ in the intervals [1.0, 1.1] and [1.3, 1.5] TeV, and for mass-degenerate W′ and Z′ in the interval [1.0, 1.7] TeV.